Strategy for Development of the Kapopo Natural Tourism Area, Ngatabaru Village, Sigi Bureaumaru District, Sigi Regency - Haris Abdul Kadir; Sarifuddin. T; Rasmi Nur Anggraeni; Wahba; Zainal Abdi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
In order to measure the effectiveness of the Kapopo natural tourism area management policy, a SWOT analysis tool is used for the strategic environment, namely the internal and external environment. Analysis of internal factors (IFAS) shows that the Strengths factor has a total value of 1.84 and Weaknesses has a total value of 0.8, while the total value of the entire IFAS table is 2.64. Analysis of external factors (EFAS) shows that the opportunity value is 2.1 and the threat value is 1.1, while the total value of the EFAS table is 3.2. The projection of the Internal and External factor values into the SWOT analysis diagram shows that the Kapopo natural tourism area is in quadrant I, which means that the management strategy currently implemented is growth oriented (Growth Oriented Strategy). Further analysis using the IE Matrix shows that the value of the Internal External factors of the Kapopo natural tourism area is in cell 2, namely a growth strategy with concentration through horizontal integration. The SWOT matrix produces policy formulations with several strategies, namely the Strategy for Maximizing Strengths and Opportunities (S-O), the Strategy for Maximizing Strengths and Minimizing Threats (S-T), the Strategy for Minimizing Weaknesses and Maximizing Opportunities (W-O), and the Strategy for Minimizing Weaknesses and Minimizing Threats (W-T)